VALIDASI AWAL TEKNOLOGI PENENTUAN WAKTU TANAM LAHAN SAWAH TADAH HUJAN “WeRise” MENGGUNAKAN VARIETAS UNGGUL INPARI 41 - Nurwulan Agustiani; Sujinah Sujinah; Z. M. Hikmah; L. Hadiawati; Samijan Samijan; Y. Kamal; M. I. Wahab; L. Lliorca; K. Hayashi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2021)
WeRise is a rainfed specific technology (IRRI-JIRCAS-IAARD) that helps farmers to determine planting time according to rainfall distribution and specific variety. The research was conducted in West Nusa Tenggara (WNT) and Central Java at 2018, involving 15 farmers in each location. It compared planting time according to WeRise’s recommendation (1) and farmers’ practice (2), using the same variety, namely Inpari 41, which is a specific high yielding variety for rainfed. It was analyzed using the T test at the 5% level. The best WeRise’s recommendations in WNT was ± 1 December 2018, while farmers’ planting time was carried out on ± 15 November 2018. Meanwhile, in Central Java WeRise’s recommendations was same as the farmers, on ± 15 November 2018. However, testing was still carried out following the second / third alternative WeRise recommendation even though the yield prediction were lower (1 December 2018). The yield from WeRise treatment and farmer practices was not significantly different with an average yield of 5.01 t ha-1 for the WeRise treatment and 4.84 t ha-1 for farmer practice in Central Java and an average yield of 5.44 t ha-1 for the WeRise treatment and 5.65 t ha-1 for farmer practice in WNT. This means that in this initial validation WeRise had shown a fairly good performance with equivalent yield to farmers. However, it was suspected that Werise’s prediction in Central Java was still too low or 54% lower than the actual yield, while the prediction in NTB reaches 102%.